An Analysis of Abrupt Change in Rainfall and the Occurrence of Extreme Events - Rahmat, Siti Nazahiyah (International Journal of Integrated Engineering, 2019)
Extreme events are normally apparent as they considerably and deviate from the normal condition. In some parts of the world increases in extreme events are apparent, while in others there appears to be a decline. It is of great attention to explore and understand the changes (if any) for an area from the previous history before undertaking any further studies. These abrupt changes may indicate a shift into another rainfall regime. In the current study, abrupt changes in historic rainfall variability were investigated using Sequential Mann-Kendall test at five (5) selected stations. Four out of the five stations (Edenhope, Kerang, Malmsbury and Yanac) selected showed significant abrupt increases in rainfall. The Melbourne Regional Office (MRO) station identified an abrupt increase in 1916, however, it was not significant. In addition, Standardised Precipitation Index (SPI) was applied to identify the historical extreme events, namely droughts and floods. It is observed that the annual rainfall had an increasing change in early 1990s due to flood events. The floods of 1946 was one of the worst events recorded in history and most of the stations undergone large increases in rainfall. This study reveals that the Sequential Mann-Kendall test detected the change point well and the results were consistent with the SPI.